PERTANGGUNGJAWABAN DEWAN PERWAKILAN RAKYAT DAERAH SEBAGAI SALAH SATU UNSUR PENYELENGGARA PEMERINTAHAN DAERAH - , LILIS MARYATI, SH ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aimed to assess the accountability of the Regional House of Representatives as the element of the Regional Governance, and to examine whether the Regional House of Representatives as as the element of the Regional Governance would need to provide an accountability and howit was regulated in laws and regulations. This was a normative research which was designed to discover the principles and legal synchronization of legislation governing the accountability of the Regional House of Representatives as the elementof the Regional Governance. The Act No. 32 of 2004 require institutional relation among the head of regional government and the Regional House of Representatives as equal partners in conducting their duties in governance and regional autonomy. Therefore, both the of regional government and the Regional House of Representativesare given the same responsibility of regional governance to realize an efficient, effective, transparent and accountable in order to provide the best possible service to the community by ensuring the productivity and welfare in the region. Moreover, as regional representative institutions, the Regional House of Representatives has 3 (three) functions as a representative in the framework, namely the legislating, budgeting, and oversight functions. The results showed that the laws and regulations governing the liability of the Regional House of Representatives just a member accountability, not as an element of the regional governance.